Functional outcomes in older patients after Parkinson’s disease diagnosis in Japan: The LIFE study - Masayo Komatsu; Sanyu Ge; Yasuyoshi Kimura; Ling Zha; Nobuhiro Narii; Yuki Okita; Yoshimitsu Shimomura; Yasufumi Gon; Fumiko Murata; Megumi Maeda; Sho Komukai; Kosuke Kiyohara; et al. (Clinical Parkinsonism & Related Disorders)
Background: The association between care needs level (CNL) and functional outcomes after diagnosis in older patients with Parkinson’s disease (PD) is unclear. Methods: Using health insurance claims and the Japanese Long-Term Care (LTC) data from 12 municipalities in Japan, PD patients aged ≥ 65 years old were identified between April 2014 and March 2022. CNL was classified as no care needed (NCN), support level (SL), CNL1 (low level), CNL2-3, and CNL4-5 (fully dependent) based on the total estimated daily care hours as defined by the national standard criteria. The primary outcomes were changes in CNL and all-cause death one year after PD diagnosis by baseline CNL at diagnosis. Results: Of the 11,270 PD patients, 39.8% had NCN, 27.6% SL&CNL1, 18.8% CNL2-3, and13.9% CNL4-5 at PD diagnosis. One-year after diagnosis, there were NCN 28.2%, SL&CNL1 24.9%, CNL2-3 19.2%, CNL4-5 17.6% (i.e., 61.7% required care need), and all-cause death 10.1%. Compared with NCN patients at diagnosis, patients with SL&CNL1, CNL2-3, and CNL4-5 had an increased risk of all-cause death one-year after diagnosis (adjusted hazard ratio [95% confidence interval]: 1.58 [1.29–1.93], 2.83 [2.32–3.46], and 5.80 [4.76–7.06]), assessed by using Cox proportional hazard models. Conclusions: Baseline CNL in older Japanese patients was associated with all-cause death even one-year after PD diagnosis, and high CNL was associated with a high risk of all-cause death.